PENINGKATAN KEAKTIFAN SISWA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS IIA SD NEGERI KARANGNYAR GUNUNG 02 - Ni'matul Cholidah; Mudzanantun; Anastasia Yeni Himawati (LPPM Universitas Cipta Mandiri, 2024)
This classroom action research aims to enhance the engagement of Class IIA students in Pancasila and Citizenship Education at Karanganyar Gunung 02 State Elementary School, employing the Problem Based Learning (PBL) model aided by interactive envelope media. The study involved 26 Class IIA students as its subjects. The research focused on the learning activity of these students in Pancasila and Citizenship Education at Karanganyar Gunung 02 State Elementary School. The initial observation in Cycle I revealed an average score of 19 with a 64% student activity rate, indicating a fairly active participation. Subsequent observation in Cycle II demonstrated an increased average score of 22 with a corresponding 75% student activity rate, classifying the student engagement as active. Consequently, the study concludes that the utilization of the Problem Based Learning (PBL) model, complemented by interactive envelope media, contributes to an 11% increase in the learning activity of Class IIA students at Karanganyar Gunung 02 State Elementary School, evident in both Cycle I and Cycle II.